Factors associated with attitude regarding the Ebola Virus disease among medical and nursing students in a Nigerian teaching hospital - Balami, Lawan Gana; Ismail, Suriani; M. Saliluddin, Suhainizam; Garba, S. H. (Community Health Society Malaysia, 2016)
Background: In recent times the Ebola Virus Disease has been a major source of public health concern. The 2014 West African outbreak affected several Health Care Workers (HCW) and this has negatively affected their attitudes towards the disease. Materials and Methods: This cross-sectional study was done at the University of Maiduguri Teaching Hospital (UMTH), Nigeria and involved 423 under-graduate medical and nursing students. Multi-stage stratified random sampling was used and data was collected using a pretested structured self-administered questionnaire. Data analysis was done using IBM-SPSS version 22. Association between two categorical variables was done using Chi-square test, while Spearman’s correlation was used for correlation between two continuous as well as ordinal variables. The predictors of attitude were analyzed using Multiple Logistic Regression. Result: The mean attitude score was 83.9 ±9.8, about 51.8% had good attitude. Predictors of attitude were age (AOR = 1.099, 95% CI = 1.019 - 1.184), field of study (AOR = 1.953, 95% CI = 1.142 – 3.334) and fifth year of studies (AOR = 1.993, 95% CI = 1.081 – 3.677). Conclusion: Negative attitudes still exist such as fear of infection as well as stigmatization of EVD patients and survivors. There is need for government intervention through funding to improve the situation.